2015
DOI: 10.1128/iai.00926-15
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytic Iron Deficiency Enhances Susceptibility to Plasmodium chabaudi Infection in Mice Carrying a Missense Mutation in Transferrin Receptor 1

Abstract: The treatment of iron deficiency in areas of high malaria transmission is complicated by evidence which suggests that iron deficiency anemia protects against malaria, while iron supplementation increases malaria risk. Iron deficiency anemia results in an array of pathologies, including reduced systemic iron bioavailability and abnormal erythrocyte physiology; however, the mechanisms by which these pathologies influence malaria infection are not well defined. In the present study, the response to malaria infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Both altered iron bioavailability and erythrocyte physiology have been implicated as mechanisms underlying the putative protective effect of iron deficiency [ 19 , 40 ]. Clark et al speculated that iron deficiency might induce a reduction in the erythropoietic rate and the synthesis of microcytic, iron-deficient erythrocytes unsuitable as host cells for the parasites [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both altered iron bioavailability and erythrocyte physiology have been implicated as mechanisms underlying the putative protective effect of iron deficiency [ 19 , 40 ]. Clark et al speculated that iron deficiency might induce a reduction in the erythropoietic rate and the synthesis of microcytic, iron-deficient erythrocytes unsuitable as host cells for the parasites [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, these difficulties can be overcome in studies of experimental animal models of malaria, as these allow full control over the cause, degree, and alleviation of iron deficiency, as well as control over the timing and clinical consequences of malaria infection in iron-deficient and iron-replete animals. Nevertheless, such studies have also shown conflicting results [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…TF, an acute‐phase protein synthesized in the liver, is mainly involved in binding and transportation of iron in the blood circulation. Decreased levels of TF have been associated with diabetes mellitus , inflammation and infection . Furthermore, TF has been postulated to control oxidative stress by increasing uptake of iron .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TFRC gene (i.e., transferrin receptor) encodes a cell surface receptor necessary for cellular iron uptake, which is essential for development of red blood cells [ 18 ]. And iron deficiency anemia is observed in a mouse model of missense mutation in TFRC [ 19 ]. As another example, PICALM gene (i.e., phosphatidylinositol binding clathrin assembly) interacts with TFRC as a critical regulator of transferrin receptor endocytosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%